ANXIETY-DEPRESSIVE DISORDER IN PATIENTS WITH BORDERLINE PERSONALITY DISORDER: CLINICAL MANIFESTATIONS, TRIGGERS, AND EASING FACTORS - Bondarenko , Yaroslav; Mozgova , Tetiana (Collection of scientific papers «ΛΌГOΣ», 2025)
Relevance: Anxiety-depressive disorder in patients with borderline personality disorder (BPD) is a common and complex consequence that affects daily life, especially in individuals aged 16-25. This period is often marked by identity crises, social and personal conflicts, and the emotional burden can lead to severe outcomes, such as prolonged depression, suicidal thoughts, and neurotic states. Investigating the clinical manifestations of this disorder, the triggers of exacerbations, and factors that alleviate the condition is crucial for developing effective approaches to managing, curating, and treating such patients.